High-throughput assessment of the behavioral responses to toxic organic solvents in Caenorhabditis elegans - Masahiro Tomioka (PLoS ONE, 2025)
Novel chemical compounds are continuously being developed for use in various industries and daily life. Workers in these industries assess and avoid chemical hazards based on published information about chemical toxicities. However, avoiding the hazards associated with chemicals with unknown toxicity is difficult. Therefore, understanding the toxicities of chemicals in a high-throughput, multifaceted manner is essential. In this study, I developed a high-throughput method for assessing chemical toxicities through quantitative measurement of behavior in Caenorhabditis elegans. I determined the acute response to 30 organic solvents, including alcohols, cellosolves, ethers, ketones, and acetate esters, which are widely used in industries, with motility as an endpoint. Exposure to 0.5%–6% organic solvents caused a dramatic decrease in locomotion speed. The adverse effects of organic solvents on motility were proportional to the lipid solubility of the chemicals, similar to the positive relationship between the anesthetic effects of volatile organic chemicals and their lipid solubility in organisms, including humans. In addition to their effects on motility, organic solvents affect posture during locomotion in different ways depending on the chemical’s functional group. Solvents with hydroxyl groups, such as alcohols and cellosolves (0.5%–3%), reduced the amplitude of body bending, whereas solvents with ketone groups, such as ketones and acetate esters (0.5%–4%), increased it during undulatory locomotion. In addition, organic solvents caused changes in chemotaxis plasticity based on the association between starvation and chemical signals at concentrations lower than those that affect locomotion. This study describes a high-throughput method for acute chemical toxicity testing and provides new insights into behavioral responses to organic solvents that are toxic to humans and other animals.